The protective role of EP300 in monocrotaline-induced pulmonary hypertension - Yang, Lei; Tian, Jinglin; Wang, Jun; Zeng, Jie; Wang, Ting; Lin, Boya; Linneman, John; Li, Li; Niu, Yanqin; Gou, Deming; Zhang, Yunhui (Frontiers in Cardiovascular Medicine, 2023)
Background: Pulmonary hypertension (PH) is a lethal disease characterized by pulmonary vascular remodeling, which is mediated by the abnormal proliferation/migration of pulmonary arterial smooth muscle cells (PASMCs). Recent reports suggest the involvement of histone acetylation in PAH development and that histone deacetylase (HDAC) inhibitors have therapeutic potential for the treatment of PAH. EP300 is an acetyltransferase that plays diverse roles in cell proliferation, differentiation, and apoptosis. However, the functions of EP3000 in PH are rarely studied. Results: In this work, we found that the expression of EP300 was increased in the pulmonary arteries of monocrotaline (MCT)-induced PH rats. Knockdown of EP300 by AAV-mediated shRNA exacerbated the PH, with a higher right ventricular systolic pressure (RVSP), right ventricular hypertrophy index (RVHI), and wall thickness in the pulmonary artery of MCT-induced PH rat. On the cellular level, the proliferation of PASMCs was promoted by EP300 knockdown. In addition, the expression of EP300 was increased in PASMCs by the overexpression of EGR1, while the deletion of EGR1 binding sites in the EP300 promoter region decreased the activity of EP300 promoter. Moreover, deleting the EP300 promoter region containing EGR1 binding sites using CRISPR/Cas9 abolished the upregulation of EP300 in MCT-induced rats and exacerbated MCT-induced PH. To summarize, our data indicate that EP300 upregulation mediated by EGR1 has a protective effect on MCT-induced PH. Conclusions: These findings showed EP300 expression was increased in the MCT-induced PH model in rats, which could be mediated by EGR1; the EP300 also displayed the potential to provide protection from PH.